National genetic evaluation (system) of hanwoo (korean native cattle) - Park, B (Asian-Australasian journal of animal sciences, 2013)
Hanwoo (Also known as Korean native cattle; Bos taurus coreanae) have been used for transportation and farming for a long time in South Korea. It has been about 30 yrs since Hanwoo improvement began in earnest as beef cattle for meat yield. The purpose of this study was to determine the trend of improvement as well as to estimate genetic parameters of the traits being used for seedstock selection based on the data collected from the past. Hanwoo proven bulls in South Korea are currently selected through performance and progeny tests. National Hanwoo genetic evaluations are implemented with yearling weight (YW), carcass weight (CW), eye muscle area (EMA), backfat thickness (BF) and marbling score (MS). Yearling weights and MS are used for selecting young bulls, and EMA, BF, and MS are used for selecting proven bulls. One individual per testing room was used for performance tests, and five individuals per room for progeny tests. Individuals tested were not allowed to graze pasture, but there was enough space for them to move around in the testing room. Feeds including roughages and minerals were fed ad libitum, and concentrates were provided at the rate of about 1.8% of individual weight. Overall means of the traits were 352.8±38.56 kg, 335.09±44.61 kg, 77.85±8.838 cm(2), 8.6±3.7 mm and 3.293±1.648 for YW, CW, EMA, BF and MS. Heritabilities estimated in this study were 0.30, 0.30, 0.42, 0.50 and 0.63 in YW, CW, EMA, BF and MS, respectively, which are similar to results from previous research. Yearling weight was 315.54 kg in 1998, and had increased to 355.06 kg in 2011, resulting in about 40 kg of improvement over 13 yrs. YW and CW have improved remarkably over the past 15 yrs. Breeding values between 1996 and 2000 decreased or did not change much, but have moved in a desirable direction since 2001. These improvements correspond with the substantial increase in use of animal models since the late 1990s in Korea. Hanwoo testing programs have practically contributed to the improvement in aspects of quality and quantity. In sum, the current selection system is good enough to accommodate circumstances where fewer sires are used on many more cows. Although progeny tests take longer and cost more, they seem to be appropriate under the circumstances of the domestic market with its higher requirement for better meat quality. Consequently, accumulative data collection, genetic evaluation model development, revision of selection indices, as well as cooperation among farms, associations, National Agricultural Cooperative Federation, universities, research institutes, and government agencies must be applied to the Hanwoo selection program. All these efforts will assist the domestic market to secure a competitive position against imported beef under Free Trade Agreement trade system and will provide farmers with higher profits as well as the public with a higher quality of beef